It's our job to care for SE. - Wing, Michael (Software engineering notes.)
I want software engineering to become a great and enduring profession. Alas, this topic is too large for one essay, so here I focus on the notion that "it is our job to care for SE." This can be restated as "we must be true to ourselves" or "success" comes from within" or "we are responsible for our own success." I believe that most of what I write here is obvious, but I believe it warrants a closer look and I want to say it clearly.